Comparison of cardiac troponin in postmortem blood sample of sudden cardiac death and non-cardiac death - Sharija , S; Sasikala, K; Sarathkumar, A; Nikita Prabhakaran , G (Journal of Indian Academy of Forensic Medicine, 2019)
Sudden Cardiac Death (SCD) contributes to 80 % of sudden deaths. Postmortem diagnosis based on changes in heart is difficult if  death occurs at an early stage. Estimation of cardiac Troponin I would be useful. Present study was to find out cTn I level in post mortem blood sample. This cross-sectional study was conducted on 55 cases of cardiac death and non cardiac death with comparison  between groups for a period of one year after Institutional Ethics Committee clearance. During autopsy, blood samples were collected  and Troponin I estimation was done. Association between the variables were checked using Chi-square test for qualitative variables  and student 't' test for continuous variables. Serum Troponin I level among Cardiac Death was 11.1 (SD 13.3) while it was 0.8 (SD 0.7)  in Non-Cardiac Death. Optimum cut off value of Troponin I was >1.1 ng/ml with a sensitivity of 98.18 and specificity 87.27. The  variation in Troponin I values were significantly different in both groups. Serum Cardiac Troponin I was found to be a good predictor  of the SCD.
Keywords: Sudden Cardiac Death (SCD); Non Cardiac Death (NCD); Cardiac Troponin I (CTn I); Coronary Artery Disease (CAD); Myocardial Infarction(MI); Body Mass Index (BMI)